2014
DOI: 10.1155/2014/628476
|View full text |Cite
|
Sign up to set email alerts
|

Different Profile of Serum Leptin between Early Onset and Late Onset Preeclampsia

Abstract: Aim. This study was designed to clarify the role of leptin and adiponectin in preeclampsia (PE) pathogenesis and different subtypes of preeclampsia. Method. This case control study was performed in 45 PE patients and 45 healthy controls matched for age, BMI, and ethnicity. Serum leptin and adiponectin levels were determined by enzyme linked immunosorbent assay (ELISA). Results. Maternal serum leptin and adiponectin were significantly higher in PE women than controls. Serum leptin was elevated in early onset pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
2
25
1
Order By: Relevance
“…There have been studies reporting that higher serum leptin is observed in preeclamptic patients compared to normal pregnancies [29,30]. In addition to this, serum LEP has been reported to be higher in early-onset PE compared to late-onset PE [31]. This, however, contrasts with others who did not find any correlation between leptin expression with PE [32].…”
Section: Discussionmentioning
confidence: 92%
“…There have been studies reporting that higher serum leptin is observed in preeclamptic patients compared to normal pregnancies [29,30]. In addition to this, serum LEP has been reported to be higher in early-onset PE compared to late-onset PE [31]. This, however, contrasts with others who did not find any correlation between leptin expression with PE [32].…”
Section: Discussionmentioning
confidence: 92%
“…Leptin is particularly well studied in the context of pregnancy. This hormone, produced by both adipocytes and the placenta, increases linearly throughout gestation, and abnormally elevated leptin levels have been consistently associated with pathologic pregnancies, including gestational diabetes mellitus and preeclampsia [36,157]. The leptin receptor is found on both innate and adaptive immune cells, and a variety of early observational in vitro studies have linked it with pathologic inflammation (such as that seen in autoimmune diseases and chronic obesity), differentiation of pro-inflammatory Th17 cells, and inhibition of the differentiation of Tregs [40,127,138].…”
Section: Metabolic Regulation Of Immune Responses In Pregnancymentioning
confidence: 99%
“…Preeclampsia is a heterogeneous disorder with two subtypes that have been described based on the timing of disease onset (early and late onset of preeclampsia), and several risk factors for preeclamptic development differed significantly in their association with early versus late onset (Rolfo et al, ; Aksornphusitaphong and Phupong, ; Lisonkova and Joseph, ; Salimi et al, ). We evaluated the mRNA and protein expression of PiT‐1 and PiT‐2 in preterm (early‐onset) or term (late‐onset) labor.…”
Section: Discussionmentioning
confidence: 99%